2014
DOI: 10.1063/1.4891597
|View full text |Cite
|
Sign up to set email alerts
|

Double functions of porous TiO2 electrodes on CH3NH3PbI3 perovskite solar cells: Enhancement of perovskite crystal transformation and prohibition of short circuiting

Abstract: In order to analyze the crystal transformation from hexagonal PbI2 to CH3NH3PbI3 by the sequential (two-step) deposition process, perovskite CH3NH3PbI3 layers were deposited on flat and/or porous TiO2 layers. Although the narrower pores using small nanoparticles prohibited the effective transformation, the porous-TiO2 matrix was able to help the crystal transformation of PbI2 to CH3NH3PbI3 by sequential two-step deposition. The resulting PbI2 crystals in porous TiO2 electrodes did not deteriorate the photovolt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 18 publications
5
53
0
Order By: Relevance
“…It was confirmed that although inorganic HTM can work effectively as organic HTM, CuSCN can react with CH3NH3PbI3. Therefore, porous TiO2 is necessary to block short circuits [9]. In order to achieve concrete results, further experiments should be done, for example TEM, XPS, SEM, Auger spectroscopy, X-ray absorption fine structure (XASF), and so on.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was confirmed that although inorganic HTM can work effectively as organic HTM, CuSCN can react with CH3NH3PbI3. Therefore, porous TiO2 is necessary to block short circuits [9]. In order to achieve concrete results, further experiments should be done, for example TEM, XPS, SEM, Auger spectroscopy, X-ray absorption fine structure (XASF), and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the XRD patterns of the two-step deposition of the CH3NH3PbI3 perovskite crystal with the HTM layer. Due to the procedure of the two-step sequential deposition of the PbI2 crystal into methylammonium iodide solution, some part of the PbI2 can remain [9]. Although the CuSCN XRD peak can remain on the one-step deposited CH3NH3PbI3 (15.8°, in Figure 2), it was found that the peak of CuSCN vanished on the two-step-deposited CH3NH3PbI3 perovskite layer, which may be due to the attack of the excess amount of iodide ion from the PbI2 layer on the CuSCN crystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Further studies of this sort will be very insightful with respect to the device stability, in particular, if they were to include relevant stressors such as moisture, oxygen, and UV light. A range of inorganic hole-transporter materials were proposed with the aim of improving the device stability, including copper thiocyanate (CuSCN), [34][35][36][37][38][39][40][41] copper iodide (CuI), 42,43 and nickel oxide (NiO x ). 44 The latter for example showed good stability over 60 days, during which control devices with spiro-OMeTAD underwent rapid degradation.…”
mentioning
confidence: 99%
“…The device showed a slight enhancement in performance to display a PCE of 5.12% and exhibited stability against light soaking without encapsulation. A remarkable improvement under the same configuration was further achieved by the sequential deposition method [129] and preheating substrate before PbI 2 deposition. The efficiency was enhanced to 10.51% because of a pinhole-less perovskite layer which limits the diffusion of CuSCN into the CH 3 NH 3 PbI 3 active layer [130].…”
Section: Meoporous Cuscn-based N-i-p Pscsmentioning
confidence: 82%